FIELD SCHOOL OF ORGANIC FARMING AS AN EFFORT TO INCREASE ORGANIC RICE PRODUCTION - Hasanah, Yaya; Hanum, Hamidah; Rusmarilin, Herla (Journal of Saintech Transfer, 2019)
The increase in people's healthy life style has increased the demand for organic rice. However, this is not supported by sufficient increase in the organic rice production. Therefore, Field School of Organic Farming (FS-OF) was conducted as an effort to increase the organic rice production. This FS-OF activity is aimed to improve farmers' understanding and skill about the organic rice cultivation through demonstration plots. The service activities that have been carried out include the production of demonstration plots for organic and conventional rice cultivation to compare their production, handover of technology transfer tools, training in organic rice cultivation, making the liquid organic fertilizers and organic pesticides, and biochar. The results of community service have increased the understanding of field school participants and increased organic rice production by 10% when compared to conventional rice cultivation